2008
DOI: 10.1002/art.23429
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA‐146 in rheumatoid arthritis synovial tissue

Abstract: Objective Several microRNA, which are ∼22‐nucleotide noncoding RNAs, exhibit tissue‐specific or developmental stage–specific expression patterns and are associated with human diseases. The objective of this study was to identify the expression pattern of microRNA‐146 (miR‐146) in synovial tissue from patients with rheumatoid arthritis (RA). Methods The expression of miR‐146 in synovial tissue from 5 patients with RA, 5 patients with osteoarthritis (OA), and 1 normal subject was analyzed by quantitative reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
429
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 556 publications
(471 citation statements)
references
References 34 publications
(34 reference statements)
26
429
1
6
Order By: Relevance
“…For example, reducing the activity of C. elegans linage 4 (lin-4) miRNA shortens lifespan, whereas overexpression of lin-4 extends lifespan (55,56). Interestingly, two groups reported that the expression pattern of miR-155 and miR-146 miRNAs is altered in synovial tissue in RA, suggesting a potential role of miRNA in the pathogenesis of other disorders acquired with age (57,58).…”
Section: Cross-talk Between Epigenetics Aging and Late-life Diseasesmentioning
confidence: 99%
“…For example, reducing the activity of C. elegans linage 4 (lin-4) miRNA shortens lifespan, whereas overexpression of lin-4 extends lifespan (55,56). Interestingly, two groups reported that the expression pattern of miR-155 and miR-146 miRNAs is altered in synovial tissue in RA, suggesting a potential role of miRNA in the pathogenesis of other disorders acquired with age (57,58).…”
Section: Cross-talk Between Epigenetics Aging and Late-life Diseasesmentioning
confidence: 99%
“…Elevated miR-146 expression levels, which are likely to reflect the infiltration of inflammatory cells and increased levels of mediators tumor necrosis factor (TNF)-α and IL-1β, were found in tissues related to chronic inflammatory diseases such as psoriasis and rheumatoid arthritis. 17 In addition, miR-146a is an important modulator of innate immune cell differentiation and function, as well as adaptive immunity. In monocytes, miR-146a attenuates TLR4 signaling and contributes to endotoxin tolerance by targeting TRAF6 and IRAK1.…”
Section: Introductionmentioning
confidence: 99%
“…10 Dysregulation of miRNAs can lead to autoimmune diseases, such as rheumatoid arthritis (RA) and multiple sclerosis (MS). 11,12 Although miRNA regulation of each target results in small changes in gene expression, the network activity of miRNAs affecting hundreds of genes simultaneously can produce dramatic changes in cell behavior. 13 We have recently reported that downregulation of miR-126-3p and miR-145-5p promotes CD4 + and CD8 + T-cell activation by increasing MYC and PIK3R2 expression levels in AA patients.…”
Section: Introductionmentioning
confidence: 99%